THE CREATION OF AN INDEPENDENT CURRICULUM IMPLEMENTATION TEACHING MODULE ACTION SHEET TEACHING MODULE FOUNDATION PHASE - Novi Andriyati; Alya Afifah Syaifia Putri; Siti Kania; Wulan Seftyani; Nova Yuliana Sari; Umi Isnawati; Cep Unang Wardaya; Chandra Apriyansyah (Universitas Panca Sakti Bekasi, 2024)
Community service provides a real opportunity for students to apply the values of Pancasila in the context of everyday life. Through this project, it is hoped that students will not only hear or understand concepts, but also experience firsthand how these values can enrich life together. Making teaching modules is an effective strategy to integrate Pancasila values into the learning process. Teaching modules provide systematic and structured guidance for teachers and learners to explore these values through varied learning methods. The author conducted this study to find out how teacher involvement in making teaching modules, aligning teaching modules with the principles of the Independent Curriculum. The method of approach for the implementation of community service activities includes seminars, workshops, and mentoring. The partners involved are representatives of kindergarten teachers in Garut Kota and Tarogong Kidul districts, totaling 50 people. The results of the evaluation of this activity were classified as effective with the achievement of 74% of the total responses of teachers who had done post-test with an increase of 26% from the responses of teachers who did not pass the pre-test. Based on the results of the teaching module preparation assignments collected, around 74% of participants already understand the components of preparing teaching modules based on the Independent Curriculum.